Zimbabwe Presidential Election, 9 to 11 March 2002 : report (Commonwealth Secretariat LondonGB, 2002)
Presents the political background. Looks at aspects such as the electoral framework and preparations for the elections; the campaign and the media; and, the poll and the count.
Keywords: ELECTIONS